Perspektif Budaya Hukum dan Pluralisme Hukum pada Kelompok Ahmadiyah di Indonesia - Oktaviana, Prabawati; Andriana, Vegia; Harahap, Chisa Belinda (Gunung Djati Conference Series, 2025)
Law is a reflection of the system of cultural values in society so there is a merger between law and culture known as legal culture. A country may use not only one legal system known as legal pluralism. According to Griffiths, there are two types of legal pluralism, namely strong legal pluralism and weak legal pluralism. In Indonesia, there are three legal systems, namely civil law, customary law, and Islamic law, all of which are mutually sustainable. The case that befalls the Ahmadiyah group is an example of how the application of these three legal systems in Indonesia on the one hand its existence is guaranteed by the constitution but on the other hand there are other laws that reject the existence of this Ahmadiyah group. This research aims to analyze the existence of Ahmadiyah group in Indonesia from the aspect of legal culture and legal pluralism. This research uses qualitative methods and data collection using literature study techniques by reviewing literature sources related to the research. The finding of this research is the discrimination against the Ahmadiyah group because they are considered heretical. Therefore, it is important to realize legal pluralism well in Indonesia based on three applicable legal systems and efforts are needed to strengthen an inclusive and tolerant legal culture through human rights education, interfaith dialogue, and strict legal protection.